GLOBALISASI DAN IDENTITAS KEBANGSAAN : TINJAUAN LITERATUR TENTANG TANTANGAN PENDIDIKAN DASAR DI ERA DIGITAL - Felina Sahwa Dea; Heri Effendi; Putri Natasha Suherman; Firda Marni Sulistrya; Revawista Anggelia; Suci Jondri Hasi Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Globalization has accelerated the flow of information and cultural values across borders, creating both opportunities and threats to the formation of national identity, particularly among elementary school students who are increasingly exposed to global digital content through smartphones, social media, and online entertainment. This condition raises concerns regarding the erosion of local cultural values, nationalism, and character education that should be instilled from an early age through basic education. This study aims to examine how globalization influences the development of national identity among elementary school students and to identify the challenges faced by basic education in maintaining and strengthening that identity amid the rapid advancement of digital technology. The method employed in this research is a literature review, in which the author collected, analyzed, and synthesized various relevant sources, including books, journal articles, and previous research results related to globalization, national identity, and digital-era education. The findings indicate that globalization brings both positive impacts, such as broader access to knowledge and cultural exchange, and negative impacts, including the weakening of love for the homeland, the fading of local cultural values, and the influence of foreign cultures that are not always in line with national values. Therefore, basic education holds a strategic role in strengthening national identity through the integration of character education, civic values, and local wisdom into the curriculum, supported by the wise and selective use of digital technology as a learning medium rather than merely a source of uncontrolled information.